Pengaruh Penggunaan Multimedia Interaktif, Multimedia Non Interaktif dan Minat Belajar terhadap Kompetensi Kimia Siswa MAN Cendekia Jambi - Hendrisakti Hoktovianus; Damris Muhamad; Asrial Asrial (Universitas Jambi, 2013)
Problems in learning chemistry in MAN Cendekia Jambi are the students’ grade still below theminimum completeness criteria, one way direction learning from the teacher to the students and thelack of students participation. The study aims to determine the effect of the use of interactivemultimedia, non interactive multimedia, and students learning interest on chemistry competence ofMAN Jambi students. This study uses quasi-experimental study with factorial design (3x2). The resultsshow that: 1) there are differences in the chemistry competence of students using interactivemultimedia, non-interactive multimedia, and white board media, 2) there is no difference in thechemical competence between students of high interest learning and low interest learning, and 3) thereis no interaction between media and student learning interests.